IMPLEMENTASI MUSHÄ€RAKAH MUTANÄ€QIÅžAH WAL IJÄ€RAH DALAM PEMBIAYAAN HUNIAN SYARIAH PADA PT. BANK MUAMALAT INDONESIA CABANG PONOROGO - Sarpini, Sarpini (El-Jizya : Jurnal Ekonomi Islam, 2019)
The price of a house that is increasingly expensive makes not everyone can afford it because home is one of the basic needs for everyone. Bank Muamalat Indonesia has a financing product for the home namely is financing musyÄrakah mutanÄqiÅŸah wal ijÄrah. This research is both a descriptive analysis, i.e. the author lays out all the data that includes data about the reasons to use the musyÄrakah mutanÄqiÅŸah wal ijÄrah in financing Residential Sharia in PT.Bank Muamalat Indonesia Branch Ponorogo. contract relationships and data on musyÄrakah mutanÄqiÅŸah and ijÄrah in financing Residential Sharia in PT.Bank Muamalat Indonesia Branch systematically Ponorogo, meticulous and factual with the deductive pattern i.e. a fringe theories or propositions that are common on musyÄrakah mutanÄqiÅŸah then do an analysis of the data concerning multi contract to acquire a specific conclusion.This research concluded that the reason Bank Muamalat Indonesia branch using contract Ponorogo musyÄrakah mutanÄqiÅŸah wal ijÄrah in financing the residence of Islamic Muamalat (PHSM) namely musyÄrakah mutanÄqiÅŸah wal ijÄrah is suitable for contract be used as an alternative solution in financing PHSM in Bank Muamalat Indonesia branch Ponorogo.Bank Muamalat Indonesia branch using contract Ponorogo musyÄrakah mutanÄqiÅŸah wal ijÄrah in financing the residence of Islamic Muamalat (PHSM) is reviewed from a multiple of contract that is allowed under Islamic law and does not include the category of the prohibition Hadith.The relationship contract musyÄrakah mutanÄqiÅŸah and ijÄrah in Islamic Muamalat Residential Financing (PHSM) in Bank Muamalat Indonesia branch Ponorogo i.e. Shirkat al-' Belong ' (shared ownership) and ijÄrah.